First Record of Culex (Microculex) daumastocampa (Diptera: Culicidae) in Mexico, with Notes on Cx. rejector and Cx. imitator - Garza Hernandez, Javier Alfonso (2018)
Culex (Microculex) daumastocampa Dyar & Knab was originally described by Dyar and Knab (Proc US Nat Mus 35:53–70, 1908) from larvae collected at axils of bromeliads in Port San Felipe, Panama. Culex daumastocampa is found in Colombia, Venezuela, Panama, Suriname, Costa Rica, Nicaragua, Guatemala, and Mexico, although its presence had not been reported suggesting its northernmost distribution. In Mexico, the subgenus Microculex had included Cx. rejector Dyar and Knab, and Cx. imitator Theobald. However, after that collection specimens were re-examined along with other specimens collected during 2016 in Chiapas (all specimens are available in the Culicidae Collection of the Universidad Autonoma Agraria Antonio Narro Unidad Laguna [UAAAN-UL], Mexico). Culex daumastocampa is now reported for the first time in Mexico, Cx. rejector for Chiapas, and Cx. imitator removed from the checklist of previous reports as to be present in Mexico.